The Value of People's Role in Monitoring Children's Device Use - Septiana MS; KASMI (Journal of Society, Community and Business Development, 2025)
Abstract In order to reduce barriers to children's growth and development, this study attempts to explain how parents can help prevent gadget addiction in their kids. The study was carried out in the Pringsewu Regency's Pnadansari Selatan Village Hall. Using a purposive sample technique and a descriptive qualitative approach, this study included parents who actively utilize technology and participate in their children's education at home. Observation, interviews, data reduction, and documentation were used to gather the data, which were then analyzed using the Miles and Huberman technique with triangulation for data validity. This study has significant ramifications for initiatives aimed at enhancing the standard of children's growth and development by fostering cooperation between parents and informal learning environments.